"Clicking" fragment leads to novel dual-binding cholinesterase inhibitors. (15th July 2021) - Molęda, Zuzanna; Zawadzka, Anna; Czarnocki, Zbigniew; Monjas, Leticia; Hirsch, Anna K.H.; Budzianowski, Armand; Maurin, Jan K.
Graphical abstract: Abstract: Cholinesterase inhibitors are potent therapeutics in the treatment of Alzheimer's disease. Among them, dual binding ligands have recently gained a lot of attention. We discovered novel dual-binding cholinesterase inhibitors, using "clickable" fragments, which bind to either catalytic active site (CAS) or peripheral anionic site (PAS) of the enzyme. Copper(I)-catalyzed azide-alkyne cycloaddition allowed to effectively synthesize a series of final heterodimers, and modeling and kinetic studies confirmed their ability to bind to both CAS and PAS. A potent acetylcholinesterase inhibitor with IC50 = 18 nM (compound 23g ) was discovered. A target-guided approach to link fragments by the enzyme itself was tested using butyrylcholinesterase.